Dialysis catheter management practices in Australia and New Zealand. Issue 8 (29th April 2019) - Smyth, Brendan; Kotwal, Sradha; Gallagher, Martin; Gray, Nicholas A; Polkinghorne, Kevan; ,
ABSTRACT: Aim: Dialysis catheter‐associated infections (CAI) are a serious and costly burden on patients and the health‐care system. Many approaches to minimizing catheter use and infection prophylaxis are available and the practice patterns in Australia and New Zealand are not known. We aimed to describe dialysis catheter management practices in dialysis units in Australia and New Zealand. Methods: Online survey comprising 52 questions, completed by representatives from dialysis units from both countries. Results: Of 64 contacted units, 48 (75%) responded (Australia 43, New Zealand 5), representing 79% of the dialysis population in both countries. Nephrologists (including trainees) inserted non‐tunnelled catheters at 60% and tunnelled catheters at 31% of units. Prophylactic antibiotics were given with catheter insertion at 21% of units. Heparin was the most common locking solution for both non‐tunnelled (77%) and tunnelled catheters (69%), with antimicrobial locks being predominant only in New Zealand (80%). Eight different combinations of exit site dressing were in use, with an antibiotic patch being most common (35%). All units in New Zealand and 84% of those in Australia undertook CAI surveillance. However, only 51% of those units were able to provide a figure for their most recent rate of catheter‐associated bacteraemia per 1000 catheter days. Conclusion: There is wide variation in current dialysis catheter management practice and CAI surveillance is suboptimal. Increased attention to the scope and quality of CAI surveillance is warranted and further evidence to guide infection prevention is required. SUMMARY AT A GLANCE: This study describes significant variability in management of dialysis catheters in Australia and New Zealand. The data presented might help renal units establish effective strategies for management of dialysis catheters.